Why we need a representative organization of academic PRM in Europe, and why we need it now - Gerold Stucki; Henk J. Stam; Francesca Gimigliano; Stefano Negrini (Journal of Rehabilitation Medicine)
The growing relevance of rehabilitation in healthcare to address increasing patient needs necessitates robust Physical and Rehabilitation Medicine (PRM) integration into medical education and practice. Academic PRM, rooted in medical faculties, is vital for developing the medical speciality as an academic discipline across Europe, where it faces challenges, including limited representation in medical schools and competition for resources with established disciplines. This commentary advocates establishing a representative organization for academic PRM in Europe.